On the Recursive Enumerability of Fixed-Point Combinators - Goldberg, Mayer (BRICS Report Series, 2004)
We show that the set of fixed-point combinators forms a recursively-enumerable subset of a larger set of terms that is (A) not recursively enumerable, and (B) the terms of which are observationally equivalent to fixed-point combinators in any computable context.